Autolysis and the duration of ageing on lees independently influence the aroma composition of traditional method sparkling wine. (7th November 2021) - Sawyer, S.; Longo, R.; Solomon, M.; Nicolotti, L.; Westmore, H.; Merry, A.; Gnoinski, G.; Ylia, A.; Dambergs, R.; Kerslake, F.
Abstract: Background and Aims: Yeast autolysis is understood to be primarily responsible for giving traditional method sparkling wines complex and developed aromas. The contribution from ageing the wine itself, however, is less well‐established. This study aimed to determine the contribution of autolysis products and compounds associated with wine oxidation and ageing in Vitis vinifera L. Chardonnay and Pinot Noir wines over 24 months. Methods and Results: Chardonnay and Pinot Noir base wines were tiraged, or aged with and without primary lees. Volatile composition analyses (HS‐SPME/GC/MS and GC/MS/MS) were conducted at 6, 12, and 24 months post‐bottling and sensory appraisals at 12 and 24 months. The duration of ageing significantly influenced compositional changes in fermentation‐derived and oxidative‐flavour‐associated compounds. Ageing base wines off or on lees produced similar maturation‐associated aroma profiles to sparkling wines irrespective of cultivar. Conclusions: The contribution of autolysis products did not feature as strongly as anticipated over 24 months, indicating that compounds associated with wine ageing primarily influenced the aroma of mature sparkling wines. This finding suggests winemakers ageing their wines on lees for 24 months or less should place more emphasis on base wine composition to manipulate the aroma profiles of sparkling wines. Significance of the Study: First comparative chemical compositional study of base wines concurrently with sparkling wines.